Effect of 3-Nitrooxypropanol Combined with Different Feed Additives on Growth Performance, Carcass Traits, Enteric Methane Emissions, and Physiological Responses in Feedlot Beef Cattle Fed a High-Concentrate Finishing Diet - Souza, William Luiz de [UNESP]; Niehues, Maria Betânia [UNESP]; Cardoso, Abmael da Silva; Carvalho, Victor Valério de; Perdigão, Alexandre; Acedo, Tiago Sabella; Costa, Diogo Fleury Azevedo; Tamassia, Luis Fernando Monteiro; Kindermann, Maik; Reis, Ricardo Andrade [UNESP] (MDPI, 2024)
The objective of this study was to evaluate the effect of 3-nitrooxypropanol (3-NOP) in combination with different feed additives on growth performance, carcass traits, meat quality, enteric methane (CH4) emissions, nutrient intake and digestibility, and blood parameters in feedlot beef cattle. In experiment (Exp.) 1, one hundred sixty-eight Nellore bulls (initial bodyweight (BW) 410 ± 8 kg) were allocated to 24 pens in a completely randomized block design. In Exp. 2, thirty Nellore bulls (initial BW 410 ± 3 kg) were allocated to a collective pen as one group, and treatments were allocated in a completely randomized design. Three treatments were applied: Control (CTL): monensin sodium (26 mg/kg of dry matter, DM); M3NOP: CTL with 3-NOP (100 mg/kg DM); and Combo: 3-NOP (100 mg/kg DM) with essential oils (100 mg/kg DM), 25-Hydroxy-Vitamin-D3 (0.10 mg/kg DM), organic chromium (4 mg/kg DM), and zinc (60 mg/kg DM). In Exp. 1, bulls in the Combo group had greater (p < 0.01) dry matter intake (DMI) at d 28 compared to the CTL and M3NOP groups. During d 0 to 102, bulls’ final BW and average daily gain (ADG) were greater (p ≤ 0.03) for the Combo group compared to the CTL. The bulls in the Combo and M3NOP groups had better (p < 0.01) feed conversion (FC) and feed efficiency (FE) compared to the CTL. Hot carcass weight (HCW), carcass ADG, and carcass yield were greater (p ≤ 0.05) for bulls in the Combo group compared to the CTL and M3NOP groups. The bulls in the Combo group had greater (p = 0.01) dressing compared to the M3NOP group. Combo bulls had better (p = 0.02) biological efficiency compared to the CTL. The bulls in the Combo group had lower (p < 0.01) carcass pH compared to the CTL and M3NOP groups. In Exp. 2, bulls in the Combo group had greater (p = 0.04) DMI at d 28 compared to the CTL and had greater (p < 0.01) DMI at d 102 compared to the CTL and M3NOP groups. The bulls in the Combo group had greater (p = 0.04) HCW compared to the CTL and M3NOP groups and carcass ADG was greater (p = 0.04) for bulls in the Combo group compared to the M3NOP group. The bulls in the Combo and M3NOP groups had lower (p < 0.01) CH4 production (38.8%, g/d), yield (41.1%, g/kg DMI), and intensity (40.8%, g/kg carcass ADG) and higher (p < 0.01) H2 emissions (291%, g/d) compared to the CTL. Combo bulls had lower (p < 0.01) blood glucose and insulin, and higher nutrient intake and digestibility (p ≤ 0.05) compared to the CTL and M3NOP groups. Combining 3-NOP with different feed additives improved FC and FE, and reduced enteric CH4 emissions. Combo treatment improved growth performance, carcass traits, nutrient intake, and digestibility, and improved glucose and insulin responses in feedlot beef cattle on a high-concentrate finishing diet.
Keywords: 3-nitrooxypropanol; beef nutrition; beef production; Bos indicus; carbon footprint; greenhouse gas; intensive systems; sustainable intensification; technology adoption